SUCCESS FACTORS OF MENTORING AND SUPERVISION BY HOSPITAL SUPERVISORY AGENCY - Dea Devita; Septo Pawelas Arso; Nurhasmadiar Nandini (Universitas Airlangga, 2019)
Background: A Hospital Supervisory Agency was established to assist hospitals to maintain their service quality. However, not all provinces have an effective Hospital Supervisory Agency. One of the Hospital Supervisory Agency that have run properly is Yogyakarta Provincial Hospital Supervisory Agency. Aim: This study analyzed the success factors of Yogyakarta Provincial Hospital Supervisory Agency in implementing supervision and mentoring to hospitals in Yogyakarta according to the Indonesian Government Regulation Number 49 of 2013. Methods: This study employed a secriptive-qualitative approach and was conducted in Yogyakarta from January to June 2019. Data were collected with in-depth interview to informants chosen by purposive sampling technique. Results: Yogyakarta Provincial Hospital Supervisory Agency could construct a mindset that hospitals will get benefits when partnering with them. Also, the members of Yogyakarta Provincial Hospital Supervisory Agency had strong commitment and work ethic to create innovative strategies and networking to many related stakeholders in spite of low funds from Yogyakarta Provincial Health Office or Yogyakarta Government. Conclusion: The success factors of Yogyakarta Provincial Hospital Supervisory Agency is determined by the high commitment of the members and well-built cooperation between Yogyakarta Provincial Hospital Supervisory Agencyand all hospitals in Yogyakarta. Keywords: Hospital Supervisory Board, success factors, mentoring, supervision.